169k views
1 vote
I need help understanding and finding the solution for (g(2))

I need help understanding and finding the solution for (g(2))-example-1

1 Answer

3 votes

In order to find f(g(2), we need to find g(2) first. So we have


g(2)=3(2)-5

which gives


\begin{gathered} g(2)=6-5 \\ g(2)=1 \end{gathered}

So, we have that


f(g(2))=f(1)

Then, by replacing the number 1 in the place of x on f(x), we get


f(1)=2(1)^2+1

which gives


f(1)=2+1=3

Therefore, the answer is:


f(g(2))=3

User Christopher Bonitz
by
6.2k points